DESIGN THINKING AS A PEDAGOGICAL FRAMEWORK: IMPACT ON STUDENT CREATIVITY AND PROBLEM-SOLVING - Jha, Aditi (International Journal of Research -GRANTHAALAYAH, 2025)
This paper examines the impact of design thinking (DT) as a pedagogical framework in higher education, with a specific focus on student creativity and problem-solving abilities. It investigates whether the integration of design thinking processes into teaching methodologies enhances students’ capacity to generate novel ideas, adapt to ambiguity, and address real-world challenges effectively. Drawing on a mixed-methods research design, the study analyzes quantitative measures of creativity and problem-solving, alongside qualitative reflections from students and faculty. Findings suggest that design thinking positively contributes to student learning outcomes, though challenges such as resource availability and faculty readiness remain. This paper contributes to the growing body of empirical evidence on design thinking’s effectiveness in educational contexts.